STRATEGI PENGEMBANGAN PERKEBUNAN KELAPA DALAM (Cocos nucifera Linn) SEBAGAI KOMODITI UNGGULAN DI KABUPATEN INDRAGIRI HILIR - Sisca Vaulina; Hajry Arief Wahyudy (UIR Press, 2018)
The plantation subsector was an active role to improve region economics in Indragiri Hilir Regency. This study aims to know the multiplier effect of a coconut plantation in Indragiri Hilir Regency, develop concepts and strategies for plantation development as a potential commodity in Indragiri Hilir Regency. The study used survey methods and 9 people collected as key informants, namely community leaders and coconut landowners, extension officers, and coconut farmers. Data analyzed: Multiplier effect and SWOT. The results indicated that the income of multiplier coconut plantation in 2010-2016 had fluctuated value. From the last seven years, the highest value occurred in 2011 values 1.931. Revenues obtained from the base activities coconut plantation base would increase the income of non-base activities. Base activities (coconut plantations) had the power to encourage regional economic growth. Coconut plantation in Indragiri Hilir Regency was in Quadrant III. which means coconut although it has weaknesses still has considerable opportunities to develop. However, it has the opportunity greatly to be developed. One of the methods was too minimal coconut problems to get better market opportunities. The strategy that must be applied is to encourage turn around strategy.